The relationships among positive coping style, psychological resilience, and fear of falling in older adults - Siqi Liu; Han Xiao; Peiyao Qi; Mi Song; Yuan Gao; Hongying Pi; Qingqing Su (BMC Geriatrics)
Abstract Objectives Fear of falling is a psychological issue that adversely impacts the health of elderly individuals. The purpose of this study was to investigate the correlation among positive coping styles, psychological resilience, and fear of falling in older adults. The mediating role of psychological resilience was also investigated. Methods A cross-sectional study was carried out from July 2023 to December 2023. There are 202 older adults from a tertiary hospital in Beijing, China, participated in this study. The general information questionnaire, the Simplified Coping Style Questionnaire, the Chinese version of the Connor-Davidson Resilience Scale, and the Falls Efficacy Scale-International were utilized. Descriptive statistics, Pearson correlation, and structural equation modeling were used for data analysis. Results The prevalence of fear of falling in the elderly was 53.00%. Older individuals with a history of falls or fractures had a significantly higher fear of falling (P < 0.05). Fear of falling was inversely connected with psychological resilience and positive coping styles (P < 0.05). Positive coping styles were positively connected with psychological resilience (r = 0.638, P < 0.01). Structural equation modeling showed that psychological resilience fully mediated the effect of positive coping styles on fear of falling (indirect effect estimate = -0.126, 95% CI -0.036 to-0.225; total effect estimate = -0.121, 95% CI -0.028to -0.005). Conclusion Fear of falling was widespread among older adults and psychological resilience fully mediated the relationship between positive coping styles and fear of falling. Future interventions targeting the fear of falling should consider the enhancement of psychological resilience.